Can ShortWarning Messages Reduce Speeding Behaviour? Insights from A/B Testing - Chua, Pei Ying; Liang, Andrea; Kok, Yiling; He, Ruimin (European Scientific Journal, ESJ, 2017)
Speeding increases the likelihood and severity of an accident, and is the top cause of traffic fatalities. As such, it is important to study interventions such as warning signs and messages that may be able to reduce such behaviour. The main objective of this work was to study the effects of sending short warning messages on speeding behaviour. The study design was an A/B test – drivers who were detected to have sped were randomly assigned into treatment versus control groups. The treatment groups were sent a short warning message, while the control group did not receive any message. There were two types of messages sent – Harsh and Soft. Driver speeds were monitored in the subsequent weeks after the warning was sent out, and the number of repeat offenders and speeds in each group was tracked. We found that drivers who received a warning were 1.3 times less likely to speed in the subsequent week, with the Harsh warning message being 1.6 times more effective than the Soft message. We also found that the effects of harsh messages generally persisted longer than soft messages.